You should see me in a crown (New York Push, 2021)
"You Should See Me in a Crown" by Leah Johnson is a heartwarming and empowering young adult novel that follows the journey of Liz Lighty, a talented and ambitious Black teenager who lives in the small, predominantly white town of Campbell, Indiana. Liz dreams of attending the prestigious Pennington College to pursue her aspirations of becoming a doctor, but her plans are jeopardized when she doesn't receive the scholarship she desperately needs. To secure her future, Liz decides to run for prom queen, knowing the title comes with a scholarship that could make her dreams a reality. However, Liz is not the typical prom queen candidate$1 (Bshe's introverted, not interested in the spotlight, and openly lesbian in a town where acceptance isn't always guaranteed. As she navigates the complexities of high school politics, unexpected friendships, and budding romance with her charming competition, Liz learns valuable lessons about self-acceptance, the power of community, and standing up for what she believes in. Throughout the novel, Johnson weaves together themes of identity, resilience, and the importance of embracing one's true self. "You Should See Me in a Crown" celebrates the strength found in vulnerability and the beauty of finding love and acceptance in unexpected places. It's a story that resonates with readers of all ages, offering a message of hope and empowerment in the face of adversitys
"There is no friend as loyal as a book." - Ernest Hemingway
Keywords: Leah Johnson